User awareness on security risks in M-commerce / Mohd Idzham Nawawi - Nawawi, Mohd Idzham (Faculty of Computer and Mathematical Sciences, 2007)
The growth of telecommunication and wireless networks within the last few years has been explosive, and as a result, people able to see that there is an opportunity to venture in business using this technology. Besides exchanging information, nowadays they could as well exchanging services and products through telecommunication and wireless technology. However wireless and mobility technology possess some disadvantages and risks. Among them is in terms of security. This study seek to determine the usage of m-commerce and type of business used in m-commerce particularly in Malaysia. Other than that this study also aiming to determine the level of user awareness on security risks in m-commerce. This study has been met with the objectives through series of analysis and some limitations and recommendation have been identified in improving for fiirther research in this field especially in Malaysia